What is the solution of -2a plus 3a plus 5b
3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b
The expression is: (4a+b)/(2a-5b)
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
a + 7b + 2c
√20a2b = √4a2 * √5b = 2a√5b the answer is 2a times radical 5b.
(2a - 5b)(5a - b)
10ab + 15b = 5b (2a + 3)
2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1
5b + 5b = 2 x 5b
10a - 5b = 25 So 5b = 10a - 25 and hence b = 2a - 5
a + a + a - 2a = 3a - 2a = a
2a + a = 3a
The expression is 5b + 16
An expression is a collection of numbers and letters for example 2a this is an expression 2a+5b this is also an expression